Development of methodology to test the electrical conductivity of Marandú grass seeds - de Melo, Paulo Alexandre Fernandes Rodrigues; Martins, Cibele Chalita [UNESP]; Alves, Edna Ursulino; Vieira, Roberval Daiton [UNESP] (GN1 Sistemas e Publicacoes, 2019)
The electrical conductivity test enables the evaluation of seed vigor for a maximum period of 24 hours, but the need to count the seeds to obtain a sample for analysis makes it difficult to apply this test to small seeds, such as forage grasses. The objective of this study was to establish a practical methodology for testing the electrical conductivity of Brachiaria brizantha (Hochst. Ex A. Rich.) Stapf 'Marandú' seeds and to estimate its effect on seedling emergence in the field. The water content, germination, first germination count, first emergency count, percentage, and rate of seedling emergence speed in the laboratory, seedling emergence in the field, and electrical conductivity of eight batches of seeds was analyzed. In the last test, the periods of conditioning (2, 4, 6, 8, and 24 hours) and the volumes (50 and 75 mL) of distilled water used were evaluated and a new sampling methodology based on the seed volumes, obtained with the aid of a 1.5 ml plastic tube (Eppendorf), was developed. The experimental design was completely randomized, with four replications. The electrical conductivity test using volume sampling from seeds immersed in 75 mL of water and readings taken after 2 or 4 hours was the most efficient method for evaluating the vigor of marandú grass seed batches and provided information equivalent to seedling emergence in the field.

O teste de condutividade elétrica permite a avaliação do vigor das sementes no prazo máximo de 24 horas, porém a necessidade de contar as sementes para obter a amostra para a análise dificulta a aplicação deste teste em sementes pequenas, como de gramíneas forrageiras. Objetivou-se neste trabalho estabelecer uma metodologia prática para o teste de condutividade elétrica de sementes de Brachiaria brizantha (Hochst. ex A. Rich.) Stapf. cv. Marandú visando a estimativa do vigor para a emergência de plântulas em campo. As sementes de oito lotes foram submetidas às seguintes avaliações: teor de água, germinação, primeira contagem de germinação, primeira contagem de emergência, porcentagem e índice de velocidade de emergência de plântulas em areia no laboratório, emergência de plântulas em campo e condutividade elétrica. Neste último teste foram avaliados os períodos de condicionamento (2; 4; 6, 8 e 24 horas), o volume de água destilada (50 e 75 mL) e testou-se nova metodologia de amostragem baseada no volume de sementes, obtida com o auxílio de um tubo de plástico de 1,5 mL (Eppendorf). O delineamento experimental utilizado foi o inteiramente casualizado, com quatro repetições. O teste de condutividade elétrica utilizando o método de amostragem por volume, de sementes imersas em 75 mL de água e leituras após duas ou quatro horas é eficiente na avaliação do vigor de lotes de sementes de capim-marandú, fornecendo informações equivalentes à emergência de plântulas em campo.
Keywords: Brachiaria brizantha; Forage grasses; Gramíneas forrageiras; Physiological quality; Qualidade fisiológica; Testes de vigor; Vigor tests